2009
DOI: 10.1182/blood-2009-03-208249
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype, distribution, generation, and functional and clinical relevance of Th17 cells in the human tumor environments

Abstract: IntroductionAdaptive immunity plays a crucial role in tumor immunosurveillance. [1][2][3] It has been shown that tumor-infiltrating effector T cells are associated with improved prognoses in multiple human cancers, 4-6 whereas tumor-infiltrating regulatory T (Treg) cells are negatively associated with patient outcome. 6,7 Th17 cells are newly identified effector CD4 ϩ T cells. Th17 cells and interleukin-17 (IL-17) play an active role in inflammation and autoimmune diseases. [8][9][10][11][12][13][14][15] Th17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

54
693
4
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 690 publications
(761 citation statements)
references
References 53 publications
54
693
4
10
Order By: Relevance
“…As we confirmed that human gd T cells differentiated into IL-17-producing cells, at least in the presence of IL-6, TGF-b and IL-23 (data not shown), IL-17 might be produced by gd T cells in these types of cancer. However, recent studies have shown that CD4 1 T cells were the main cellular source of IL-17 in human ovarian cancer tissues [40,41]. Therefore, in human cases, it is possible that the IL-17-producing cell subsets may vary among organs depending on the type of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As we confirmed that human gd T cells differentiated into IL-17-producing cells, at least in the presence of IL-6, TGF-b and IL-23 (data not shown), IL-17 might be produced by gd T cells in these types of cancer. However, recent studies have shown that CD4 1 T cells were the main cellular source of IL-17 in human ovarian cancer tissues [40,41]. Therefore, in human cases, it is possible that the IL-17-producing cell subsets may vary among organs depending on the type of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies in both mouse and humans have focused upon CD8+ cytotoxic T cells that kill tumors directly and T H 1 CD4+ T cells (producing IL-2, and IFN-γ) that contribute directly or indirectly to tumor killing [43]. While T H 1 remains the dominant T H subset in tumors within the memory T cell pool, another T cell subset has recently been found in both mouse and human tumors that may play a significant role in the pathogenesis of tumors [44][45][46]. This subset is a CD4+ T cell that secretes IL-17A and has been labeled as the T H 17 cell [47,48].…”
Section: Inflammatory Leukocytes In the Tumor Microenvironmentmentioning
confidence: 99%
“…Their biological role in the tumor microenvironment is poorly understood, and at present suggested to be both beneficial and detrimental to the cancer patient [51]. The generation and regulation of T H 17 cells in ovarian cancer have been documented [45] and the possible function and clinical relevance of these cells in human tumor microenvironments reported [46]. It has been postulated that T H 17 cells contribute to protective human tumor immunity by inducing the production by tumor cells of two chemokines that attract and recruit effector T cells and effector memory T cells that express CXCR3, the receptor for the T H 17 induced chemokines CXCL9 (MIG) and CXCL10 (IP10) [46].…”
Section: Inflammatory Leukocytes In the Tumor Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of Th17 cells in cancer is still unclear. The inflammatory Th17 response correlates with poor disease outcome in prostate, head and neck and colorectal cancer [28,29]. However, IL-17 knockout mice exhibited increased susceptibility to metastasis of colon cancer MC38 cells, demonstrating an possible anti-tumor function of Th17 cells [30,31].…”
Section: Introductionmentioning
confidence: 99%